The Effect of the Russian Subnational Debt on the Socio-economic Development of the Region - O. I. Larina; N. V. Moryzhenkova (Управление)
The actual problem currently in Russia is the high degree of differentiation level of socio-economic development of constituent entities of the Russian Federation. The specified uneven development is a significant problem, requiring prudent and gradual approach. An important point is to determine the optimal size and form of regional borrowing, contributing to the socio-economic development of the region. This article examines the structure of the borrowing regions. Many regions have a significant amount of borrowing in the form of budget loans. Outlines the problem caused by the miscalculations of the regional authorities when conducting its own financial policy, and a more global objective reasons, which are a consequence of the current crisis situation in economy of the Russian Federation and the disparity of economic development. The basis for the paper is drawn from actual official data describing the state of the market of regional and municipal borrowing. Used methods of system analysis, comparison and clustering.The result is proved in the article that on the one hand the issue of securities does not stimulate socio-economic development of the region, on the other hand in the current situation, the desired reduction provide budget loans should pay attention of regions in the possible form of borrowing. With the improvement of the situation on the debt market regions will be stimulated to ensure that the overwhelming proportion of their debt would be the consequence of market borrowings, primarily in the form of securities.The article presents a comparison of different forms of regional borrowing and identified deficiencies inherent in different types of borrowing. It is concluded that a bank loan is the most popular form of market borrowing, as it has in relation to issuance of bonds less amount of disadvantages. According to the authors, for the development of the bonded form of the borrowing of regions should consider the infrastructure of the state support.